Effectiveness of early intervention programs for parents of preterm infants: a meta-review of systematic reviews - Puthussery, Shuby (BMC Pediatr, 2018)
BACKGROUND: Various intervention programs exist for parents of preterm babies and some systematic reviews (SRs) have synthesised the evidence of their effectiveness. These reviews are, however, limited to specific interventions, components, or outcomes, and a comprehensive evidence base is lacking. The aim of this meta-review was to appraise and meta-synthesise the evidence from existing SRs to provide a comprehensive evidence base on the effectiveness of interventions for parents of preterm infants on parental and infant outcomes. METHODS: We conducted a comprehensive search of the following databases to identify relevant SRs: Cochrane library, Web of science, EMBASE, CINAHL, British Nursing Index, PsycINFO, Medline, ScienceDirect, Scopus, IBSS, DOAJ, ERIC, EPPI-Centre, PROSPERO, WHO Library. Additional searches were conducted using authors’ institutional libraries, Google Scholar, and the reference lists of identified reviews. Identified articles were screened in two stages against an inclusion criteria with titles and abstracts screened first followed by full-text screening. Selected SRs were appraised using the AMSTAR tool. Extracted data using a predesigned tool were synthesised narratively examining the direction of impact on outcomes. RESULTS: We found 11 SRs eligible for inclusion that synthesised a total of 343 quantitative primary studies. The average quality of the SRs was ‘medium’. Thirty four interventions were reported across the SRs with considerable heterogeneity in the structural framework and the targeted outcomes that included maternal-infant dyadic, maternal/parental, and infant outcomes. Among all interventions, Kangaroo Care (KC) showed the most frequent positive impact across outcomes (n = 19) followed by Mother Infant Transaction Program (MITP) (n = 14). Other interventions with most consistent positive impact on infant outcomes were Modified-Mother Infant Transaction Program (M-MITP) (n = 6), Infant Health and Development Program (IHDP) (n = 5) and Creating Opportunities for Parent Empowerment (COPE) (n = 5). Overall, interventions with both home and facility based components showed the most frequent positive impact across outcomes. CONCLUSIONS: Neonatal care policy and planning for preterm babies should consider the implementation of interventions with most positive impact on outcomes. The heterogeneity in interventions and outcomes calls for the development and implementation of an integrated program for parents of preterm infants with a clearly defined global set of parental and infant outcomes.